Case Report: Splenic Irradiation for the Treatment of Chronic Active Antibody-Mediated Rejection in Kidney Allograft Recipients With De Novo Donor-Specific Antibodies - Zhu, Lan; Guo, Zhiliang; Sa, Rula; Guo, Hui; Li, Junhua; Chen, Gang (Frontiers in Immunology, 2021)
Chronic active antibody-mediated rejection (AMR) in renal transplantation is usually refractory to current conventional treatment with rituximab, plasmapheresis (PP), and intravenous immunoglobulins (IVIG). Splenic irradiation has been reported to be effective in the rescue of early severe acute AMR after kidney transplantation; however, its effect in chronic AMR has not been reported to date. In order to reduce donor-specific antibody (DSA) and prevent the progression of chronic AMR, we used repetitive low-dose splenic irradiation, together with rituximab and PP/IVIG, in two living-related kidney transplant recipients with pathologically diagnosed chronic active AMR and the presence of long-term class II-de novo DSA. DSA monitoring and repeated renal biopsy revealed significantly reduced DSA levels as well as alleviated glomerulitis and peritubular capillaritis in both patients after treatment, and these therapies may have played a role in delaying the progression of chronic AMR. Although DSA levels in both patients eventually rebounded to some extent after treatment, serum creatinine increased slowly in one patient during the 16-month follow-up period and remained stable in the other during the 12-month follow-up period. Given the poor efficacy of conventional treatment at present, splenic irradiation may still be one of the treatment options for chronic AMR.